Thermal stability of copper-manganese spinel as Zero PGM catalyst for TWC application - Abken Anke Elizabeth; Golden Stephen J; Nazarpoor Zahra (2017)
Effect of the type of ZPGM material composition to improve thermal stability of ZPGM catalyst systems for TWC application is disclosed. ZPGM catalyst system samples are prepared and configured with washcoat on ceramic substrate, overcoat including doped Zirconia support oxide, and impregnation layer including either Cu1Mn2O4 spinel or Cu1Co1Mn1O4 spinel. Testing of ZPGM catalyst samples including variations of aging temperatures and different impregnation layer materials are developed under isothermal steady state sweep test condition for ZPGM catalyst systems to evaluate performance especially NOx conversions and level of thermal stability. As a result disclosed ZPGM catalyst systems with most suitable spinel that includes Cu1Co1Mn1O4 in impregnation layer exhibit high NOx conversion and significant improved thermal stability compare to Cu1Mn2O4 spinel, which is suitable for under floor and close coupled TWC application. The effect of adding Co to Cu-Mn spinel composition to improve thermal stability confirmed by TPR measurement.